Parlamentonun feshi - Çağlar, Taha Enes (My University, 2019)
Parlamentonun feshi parlamenterlerin görevine son veren ve seçimlerin yenilenmesine sebep olan önemli bir kurumdur. Öncelikli olarak parlamentonun feshi sınıflandırılmış, feshin yöntemi ve şekli açıklanmıştır. Parlamentonun feshi, yürütmeeliyle fesih, öz fesih, anayasal fesih ve halkın kararı ile fesih olarak tasnif edilebilir. Feshin yazılı şekilde yapılması kabul edilmektedir. Feshin teorisi açıklandıktan sonra feshin işlevi açıklanmaya çalışılmıştır. Feshin işlevi iki başlık altında incelenmiştir. İlk olarak fesih politik amaçlarla kullanılabilir. Fesih yetkisine sahip olan makam parlamentoyu baskı altına alabilecektir. Bu yetki parlamento çoğunluğunu belirlemek için de kullanılabilir. Feshin ikinci ve ideal işlevi ise organlar arasındaki krizleri çözmek, seçmen desteğini yenilemek ve politik konularda karar alırken seçmenin görüşüne başvurmaktır. Çalışmanın sonucunda sınırlı fesih yetkisinin uzlaşmacı demokrasiyi, takdiri fesih yetkisinin ise çoğunlukçu demokrasiyi destekleyeceğine ulaşılmıştır.

Dissolution of parliament is an important topic that terminates parliamentarian's official titles and renews general elections. First, dissolution of parliament classified and then dissolution form and procedure explained. Dissolution of parliament can be classified to executive dissolution, self-dissolution, automatic dissolution and dissolution by the people. Written procedure accepted for dissolution. After the dissolution theory is explained, the function of dissolution is tried to be explained. The function of dissolution was examined under two headings. First, dissolution power can be used for political reasons. Authority who can enjoy with dissolution power, can oppress legislative assembly. This power can use to shape legislative majority. Secondand ideal function of dissolution of parliament is solving inter powers problems, renewing mandate and learning voters view about political decisions. The conclusion of this study is that restricted dissolution power will support proportional democracy and discretionally dissolution power will give support to majoritarian democracy.
Keywords: Checks and Balances Systems; Consensus Democracy; Denge Denetim Mekanizmaları; Elections; Government Systems; Hukuk; Hükümet Sistemleri; Law; Legislative bodies; Parlamentonun Fesi; Renewal of Elections; Seçim; Seçimlerin Yenilenmesi; Uzlaşmacı Demokrasi Dissolution of Parliament; Yasama organları